The Italian Lira in the Narrow Erm Band : The Challenge of Credibility - Molho, Lazaros (Washington, D.C. : International Monetary Fund, 1991)
Under free capital mobility, a high-inflation country pursuing a nonaccommodating exchange rate policy will have higher real interest rates than its lower-inflation trading partners as long as that policy is not credible. If the policy gains credibility prior to inflation convergence, the sign of the real interest rate differential may be reversed. Developments in interest rate differentials and capital and reserve flows suggest that Italy's nonaccommodating exchange rate policy has become significantly more credible in 1989-90. As improved credibility further limits their monetary autonomy, the Italian authorities will have to rely more on fiscal and incomes policies to promote disinflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet